Gene and transposable element methylation in great tit (Parus major) brain and blood. (December 2016) - Derks, Martijn; Schachtschneider, Kyle; Madsen, Ole; Schijlen, Elio; Verhoeven, Koen; van Oers, Kees
Abstract Background Studies on vertebrate DNA methylomes have revealed a regulatory role of tissue specific DNA methylation in relation to gene expression. However, it is not well known how tissue-specific methylation varies between different functional and structural components of genes and genomes. Using whole-genome bisulfite sequencing data we here describe both CpG and non-CpG methylation profiles of whole blood and brain tissue in relation to gene features, CpG-islands (CGIs), transposable elements (TE), and their functional roles in an ecological model species, the great tit (Parus major ). Results We show that hypomethylation at the transcription start site (TSS) is enriched in genes with functional classes that relate directly to processes specific to each tissue type. We find that 6877 ( 21 %) of the CGIs are differentially methylated between blood and brain, of which 1186 and 2055 are annotated to promoter and intragenic regions, respectively. We observe that CGI methylation in promoter regions is more conserved between tissues compared to CGI methylation in intra and inter-genic regions. Differentially methylated CGIs in promoter and intragenic regions are overrepresented in genomic loci linked to development, suggesting a distinct role for CGI methylation in regulating expression during development. Additionally, we find significant non-CpG methylation in brain but not in blood with a strong preference for methylation at CpA dinucleotide sites. Finally, CpG hypermethylation of TEs is significantly stronger in brain compared to blood, but does not correlate with TE activity. Surprisingly, TEs showed significant hypomethylation in non-CpG contexts which was negatively correlated with TE expression. Conclusion The discovery that TSS methylation levels are directly linked to functional classes related to each tissue provides new insights in the regulatory role of DNA-methylation patterns. The dominant sequence motifs for brain non-CpG methylation, similar to those found in mammals, suggests that a conserved non-CpG regulatory mechanism was already present in the amniote ancestor. The negative correlation between brain non-CpG methylation and TE activity (not found for CpG methylation) suggests that non-CpG is the dominant regulatory form of methylation in TE silencing.